Hybrid fiber concrete mix proportion design and construction method and frame structure
By combining the mix ratio design of steel fiber and polypropylene fiber in concrete, performance coupling is achieved, the problems of low tensile strength and toughness of concrete are solved, the mechanical and durability of concrete are improved, and the seismic performance is improved through the application of frame structure and overall stability.
Patent Information
- Application Number
- CN202411214462.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-31
- Publication Date
- 2024-12-27
AI Technical Summary
The existing concrete has low tensile strength and poor ductility in major engineering construction, and the coupling of multiple fibers has not taken into account the improvement of concrete material performance. The single fiber design is limited to the improvement of mechanical properties, and ignores the tensile strength and durability of flexible fibers. Comprehensive improvement.
Using the mix ratio design of steel fiber and polypropylene fiber, the fiber dosage is optimized by establishing a functional relational mathematical model to achieve the performance coupling between steel fiber and polypropylene fiber, improve the tensile, bending and shear strength of concrete, and pass through the frame. The application of the structure improves seismic resistance and overall deformation ability.
It significantly improves the mechanical properties and durability of concrete, improves the seismic performance and overall stability of the frame structure, enhances the impact and fatigue resistance of concrete, reduces early shrinkage cracks and temperature cracks, and improves anti-seepage and corrosion resistance. performance.
Smart Images

Figure CN119189013A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a mixed fiber concrete mix ratio design, a construction method and a frame structure. Background Art
[0002] With the vigorous development of my country's social economy, a large number of infrastructures have been built, and the number of various super-large, super-high, and super-long concrete structures has increased year by year. my country's concrete consumption has approached 60% of the world's total. However, ordinary concrete has "short board effects" such as low tensile strength and poor ductility, which are subject to many restrictions in major engineering construction. In order to meet the different functional needs of engineering construction, scholars in the research field have been continuously committed to the modification of concrete and the research and development of high-performance concrete materials.
[0003] As one of the new building materials, fiber concrete has the following advantages. First, the addition of a moderate amount of hard high-strength fiber can effectively improve the strength index. Taking steel fiber as an example, compared with ordinary concrete, when the volume fraction of steel fiber is 1.0% to 2.0%, the tensile strength of concrete can be increased by 40% to 80%, the compressive strength can be increased by 5% to 25%, the bending strength can be increased by 50% to 150%, and the shear strength can be increased by 50% to 100%. Second, the addition of a moderate amount of lightweight flexible fiber can significantly improve the deformation capacity and tensile elastic modulus of concrete, not only improving the ultimate tensile and compressive strains to varying degrees, especially significantly slowing down the post-peak softening phenomenon, but also having a greater impact on the long-term shrinkage deformation performance of concrete, and the shrinkage rate can be reduced by 10% to 30%. Third, it makes the concrete have excellent impact resistance and fatigue resistance. In particular, the mixed fibers can play their respective advantages at different scales and stress stages, showing outstanding step-by-step crack resistance, resulting in the fracture toughness of the concrete under impact load being increased by up to about 50 times. It can also greatly reduce the early shrinkage cracks and temperature cracks of the concrete, thereby improving the concrete's durability such as anti-seepage, corrosion resistance and frost resistance.
[0004] Chinese patent CN115872681B discloses a modified polypropylene fiber concrete and its preparation method, which uses calcium carbonate powder and carbon nanotubes, combined with an organic phosphate nucleating agent, to promote the heterogeneous nucleation ability of polypropylene. This method improves the compatibility of modified polypropylene fibers in concrete, and enhances the meshing force and crack resistance of concrete. However, this method is limited to the design and application of a single fiber in the field of concrete materials, ignoring the improvement of the performance of concrete materials by coupling multiple fibers, and has not considered its application in actual engineering.
[0005] Chinese patent CN115140981B discloses high-performance graphite steel fiber concrete and its preparation method. High-performance graphite fiber concrete is formed by adding steel fiber and graphite to concrete, and graphite and steel fiber are used to improve the flexural strength and thermal conductivity of concrete. This method comprehensively considers the coupling effect of steel fiber and graphite fiber on the performance improvement of concrete, so that concrete has the advantages of good working performance and good thermal conductivity while improving mechanical properties. However, this method is limited to using high-strength hard fibers to improve the mechanical properties of concrete, and ignores the comprehensive improvement of tensile strength and durability of concrete by flexible fibers. Summary of the invention
[0006] In response to the above problems in the prior art, this application proposes a hybrid fiber concrete mix design, construction method and frame structure, which utilizes the excellent mechanical properties of steel fiber and polypropylene fiber to achieve performance coupling and superposition of hard and high-strength steel fiber and lightweight and flexible polypropylene fiber inside the concrete, solving the key performance problems of poor tensile strength and low toughness of concrete itself. On the one hand, it improves the mechanical properties and durability of concrete itself, and on the other hand, when it is recommended to be used as a disaster-prone part of the frame structure node, its seismic performance and overall deformation capacity of the structure are effectively guaranteed.
[0007] In a first aspect, the hybrid fiber concrete mix design method proposed by the present invention comprises the following steps:
[0008] Screening the raw material types of the combined fibers; the combined fibers include steel fibers and polypropylene fibers;
[0009] Select other raw materials for concrete;
[0010] The mathematical model of the functional relationship between the strength of fiber concrete and the volume fraction and size parameters of steel fibers is established: fcu,o =σ[f cu,k (1+α t ×ρ f l f / d f )]; where f fcu,o is the concrete configuration strength; σ is the safety factor; f cu,k is the target intensity; α t is the steel fiber influence coefficient; ρ f is the steel fiber volume ratio; l f is the length of steel fiber; d f is the steel fiber diameter or equivalent diameter;
[0011] Substitute the concrete mix strength and target strength into the above formula to preliminarily determine the design range of steel fiber and concrete mix ratio;
[0012] Steel-polypropylene hybrid fiber concrete specimens were prepared and the range of combined fiber content was optimized according to the flow properties to obtain the target hybrid fiber concrete.
[0013] Furthermore, after obtaining the target hybrid fiber concrete, the following steps are also included: based on the physical properties and interface geometric characteristics of the steel-polypropylene hybrid fiber concrete, combined with the actual pumping length and pumping height at the engineering site, the combined fiber content and concrete mix ratio of the target hybrid fiber concrete are directionally adjusted according to the fluidity test.
[0014] Furthermore, the blending amount of the combined fiber is not less than 0.35%;
[0015] The mass ratio of the polypropylene fiber to the steel fiber is 1:10.
[0016] Furthermore, in the functional relationship mathematical model, the safety factor σ is calculated based on the target strength f cu,k Get value;
[0017] When the target intensity f cu,k <C50, the safety factor σ=1.2; the steel fiber influence coefficient α t Take 0.5 to 0.7 according to the fiber shape;
[0018] When the target intensity f cu,k >C50, the safety factor σ=1.15; the steel fiber influence coefficient α t Take 0.5 to 1.0 according to the fiber shape.
[0019] Furthermore, other raw materials of the concrete include aggregates, cementitious materials and admixtures.
[0020] In a second aspect, the present invention proposes a frame structure, comprising beams, columns, and beam-column nodes arranged between the columns and the beams; the beam-column nodes include steel bars and concrete wrapping the steel bars, and the concrete is the target hybrid fiber concrete obtained by the above-mentioned hybrid fiber concrete mix design method.
[0021] In a third aspect, the present invention further provides a construction method of the above frame structure, comprising the following steps:
[0022] Determine the beam-column node locations of the frame structure;
[0023] Calculating the pumping length and the pumping height, and adjusting the combined fiber content and the concrete mix ratio of the target hybrid fiber concrete so that the concrete has fluidity that meets pumping conditions;
[0024] Installing a casting template for the frame structure, setting a dense mesh inside the template, embedding strain gauges on the steel bars at the beam-column node positions, and recording the deformation state of the steel bars at the beam-column node positions;
[0025] pouring the target hybrid fiber concrete into the formwork and vibrating and compacting it;
[0026] After pouring is completed, moisturizing maintenance is carried out.
[0027] Furthermore, after the step of determining the positions of the beam-column nodes of the frame structure, the step also includes: selecting some beam-column nodes of the frame structure for finite element modeling, and comparing and analyzing the stress conditions of the beam-column nodes before and after using the target hybrid fiber concrete.
[0028] Furthermore, the step of pouring the target hybrid fiber concrete into the formwork includes:
[0029] First, the target hybrid fiber concrete is poured into the template at the position corresponding to the column of the frame structure; after the concrete is initially set, the target hybrid fiber concrete is poured into the template at the position corresponding to the beam of the frame structure and the beam-column node position.
[0030] The beneficial effects of the present invention include:
[0031] (1) The present invention preliminarily determines the design range of steel fiber and concrete mix ratio by establishing a mathematical model of functional relationship, and then optimizes the combined fiber dosage range according to the flow performance to obtain the target hybrid fiber concrete, and couples the performance of high-strength and hard steel fiber and light and flexible polypropylene fiber in the field of concrete materials, so that the steel-polypropylene hybrid fiber concrete can give full play to the high-strength performance of steel fiber to improve the tensile, bending and shear strength of concrete during the stress process, and can also use the unidirectional tensile capacity of polypropylene fiber to improve the fracture toughness and ductility of the material at instantaneous failure;
[0032] (2) The material properties of steel-polypropylene hybrid fiber concrete have been comprehensively improved. The appropriate amount of hybrid fibers with different properties not only improves the mechanical properties of concrete materials, but also enhances the internal density of concrete, shrinks the ion transmission channel path, and steadily improves the durability of concrete materials;
[0033] (3) The steel-polypropylene hybrid fiber concrete is introduced into the application field of the frame structure node, which improves the seismic performance and overall stability of the frame structure. Based on the "strong node and weak component" structural design theory, the excellent mechanical properties of steel-polypropylene hybrid fiber concrete are utilized and applied to weak nodes with complex stress states and easily affected by earthquake disasters, which effectively guarantees the improvement of structural performance; therefore, the present invention has the technical advantages of simple process, scientific principle, safety and efficiency, energy saving and environmental protection in the field of waste concrete recycling, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic flow chart of the mix ratio design method of hybrid fiber concrete of the present invention;
[0035] Figure 2 It is a schematic diagram of the process of the construction method of the frame structure of the present invention;
[0036] Figure 3 This is a diagram showing the flexural and tensile properties of the hybrid fiber concrete of the present invention. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0038] like Figure 1 The hybrid fiber concrete mix design method of the present invention comprises:
[0039] Step 1: Considering that concrete has an exothermic reaction during pouring, the core area temperature peak is about 60-70°C. Therefore, when selecting the types of steel fiber and polypropylene fiber raw materials, it should be ensured that their softening point is higher than 70°C and will not be affected by the heat release during concrete hardening;
[0040] Step 2: After the types of steel fiber and polypropylene fiber are determined, select other types of raw materials for concrete, such as aggregates, cementitious materials and admixtures, according to the application scenarios and basic performance requirements of concrete. The coarse and fine aggregates are mainly crushed stone and medium sand, respectively, and the cementitious material is mainly silicate cement, which should be mixed with appropriate amounts of fly ash and mineral powder to improve the cohesion and fluidity of concrete. The admixture is determined according to actual needs, and its dosage should not exceed the allowable value in the specification;
[0041] Step 3: Concrete strength is greatly affected by steel fibers, while polypropylene fibers contribute less to mechanical properties. Therefore, a mathematical model of the functional relationship between the strength of fiber concrete and the volume fraction and size parameters of steel fibers is established. fcu,o =σ[f cu,k (1+α t ×ρ f l f / d f)], substitute the concrete mix strength and target strength into the formula to preliminarily determine the design range of steel fiber and concrete mix ratio;
[0042] In f fcu,o =σ[f cu,k (1+α t ×ρ f l f / d f )] where the steel fiber volume ratio ρ f , steel fiber length l f and steel fiber diameter d f The parameters provided by the fiber manufacturer can be obtained, so it can be regarded as a known value. The safety factor σ can be obtained according to the target strength. When the target strength is less than C50, σ = 1.2, when the target strength is greater than C50, σ = 1.15. Steel fiber influence coefficient α t According to the target strength and fiber shape, when the target strength is less than C50, α t According to the fiber shape, it can be 0.5 to 0.7. When the fiber shape is straight, α t It is better to take 0.5. When the fiber shape is hook-shaped, α t It is recommended to take 0.7, and 0.6 for those with strange shapes between the two. When the target strength is greater than C50, α t It can be taken from 0.5 to 1.0 according to the fiber shape. When the fiber shape is straight, α t It is better to take 0.5. When the fiber shape is hook-shaped, α t It is better to take 1.0, and if the shape is odd and between the two, it is better to take 0.75.
[0043] Step 4: Based on the orthogonal test, the steel-polypropylene hybrid fiber concrete specimens were quantitatively prepared to test the influence of the relative proportion of the hybrid fiber volume fraction on the flowability of concrete, and the fiber content range that can achieve good fluidity and facilitate construction while meeting the strength requirement was found, and the target hybrid fiber concrete, i.e., steel-polypropylene hybrid fiber concrete, was obtained; the combined fiber content was not less than 0.35%, and when ensuring the fluidity of concrete pumping, the combined fiber content was optimal at 2%, and when the mass ratio of polypropylene fiber to steel fiber was 1:10, the comprehensive improvement effect of concrete strength and fluidity was optimal.
[0044] Step 5: Select the scope of engineering application based on the physical properties and interface geometric characteristics of hybrid fiber concrete, combine the actual pumping length and pumping height at the project site, and adjust the composite fiber (or hybrid fiber) dosage and concrete mix ratio according to the fluidity test.
[0045] Based on the same inventive concept, the present invention also proposes a frame structure, including beams, columns, and beam-column nodes arranged between the columns and beams; the beam-column nodes include steel bars and concrete wrapping the steel bars, and the concrete adopts the target hybrid fiber concrete obtained by the above-mentioned hybrid fiber concrete mix design method.
[0046] It should be noted that the key parts of the frame structure, such as the beam-column joints, column ends, and the tension zone of the beam, as important load-bearing components and force transmission hubs, need to withstand axial forces, shear forces, and bending moments of different sizes and their combined effects. The stress state is extremely complex and is the weak link of the frame structure. It is very easy to be damaged under the action of earthquakes, which in turn affects the integrity of the structure. Both domestic and foreign seismic codes require that the frame structure be designed according to the principles of "strong columns and weak beams", "strong shear and weak bending", and "strong nodes and weak components". Usually, the seismic performance of the frame structure is enhanced by adding steel bars in the core area of key parts. However, an excessively high reinforcement ratio can easily cause congestion of steel bars at key sections, which is not only not conducive to the pouring of concrete, but also causes a decrease in the strength of the node area due to poor pouring quality.
[0047] Therefore, in view of the excellent mechanical properties of steel-polypropylene hybrid fiber concrete, in order to effectively balance the construction cost and give full play to the effect of "good steel is used on the blade", the steel-polypropylene hybrid fiber concrete obtained by the hybrid fiber concrete mix design method of the present invention is applied to the above-mentioned key parts.
[0048] like Figure 2 As shown, the construction method of the frame structure of the steel-polypropylene hybrid fiber concrete obtained by the present invention comprises the following steps:
[0049] Step 1: Based on the design principle of "strong nodes and weak components", and according to the characteristics of high tensile strength and good deformation performance of steel-polypropylene hybrid fiber concrete, the beam-column node position of the appropriate project is selected for casting and application of steel-polypropylene hybrid fiber concrete. The preliminary design uses concrete strength C30. The orthogonal design method is used to preliminarily select 4 mix ratios for testing. The test mix ratio design parameters are shown in Table 1:
[0050] Table 1 Test mix parameters of steel-polypropylene hybrid fiber concrete
[0051]
[0052] Step 2: Make standard test blocks according to specifications and standards, and calculate the pumping length and pumping height based on the strength, deformation and failure characteristics and the location of the on-site application nodes.
[0053] The optimal fiber content and mix ratio design were screened out through testing as shown in Table 2, so that the concrete has the fluidity that can meet the pumping conditions.
[0054] Table 2 Actual mix parameters of steel-polypropylene hybrid fiber concrete
[0055]
[0056] In addition, in order to make the structural stress meet the requirements of the specifications, some beam-column nodes were selected for finite element modeling, and the stress conditions of the nodes before and after the use of hybrid fiber concrete were compared and analyzed. Figure 3 The flexural and tensile strengths of two groups of test blocks of the hybrid fiber concrete of the present invention under the best mix ratio design in the field test are shown. The standard test blocks made based on the mix ratio parameters in Table 2 are tested for flexural and splitting to verify the effectiveness of the digital simulation and the rationality of the mix ratio.
[0057] Step 3: Before pouring, set a steel wire mesh from the top to the bottom of the beam at a distance of 500mm from the column edge. At the same time, symmetrically embed strain gauges on the longitudinal steel bars within 500mm of each group of beam-column nodes, 2 per group, at least three groups, to record the strain of the steel bars at the beam-column nodes during pouring and loading;
[0058] Step 4: When pouring, pour the column concrete of the frame structure first, and then continue to pour the vibrated beam concrete after it has initially set. Use a small vibrator to vibrate the area with dense steel bars to ensure that the concrete in this area is vibrated densely to avoid the formation of honeycomb surface;
[0059] Step 5: After pouring is completed, moisturizing maintenance is carried out in time. After the maintenance is completed, the surface is flat without sand and cracks. During the entire pouring and loading stage, the sensor monitors the stress strain state and deformation state of key parts in real time to ensure that the structure is loaded normally;
[0060] Step 6: Taking advantage of the rough surface of the hybrid fiber concrete and the geometric features of easily exposed fibers, proper roughening can be used to achieve a good connection with the newly poured concrete at the component location to ensure the overall performance of the structure.
[0061] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for designing a mix ratio of a hybrid fiber concrete, characterized in that: The following steps are involved: Screening the raw material types of the combined fibers; the combined fibers include steel fibers and polypropylene fibers; Select other raw materials for concrete; The mathematical model of the functional relationship between the strength of fiber concrete and the volume fraction and size parameters of steel fibers is established: fcu,o =σ[f cu,k (1+α t ×ρ f l f / d f )]; where f fcu,o is the concrete configuration strength; σ is the safety factor; f cu,k is the target intensity; α t is the steel fiber influence coefficient; ρ f is the steel fiber volume ratio; l f is the length of steel fiber; d f is the steel fiber diameter or equivalent diameter; Substitute the concrete mix strength and target strength into the above formula to preliminarily determine the design range of steel fiber and concrete mix ratio; Steel-polypropylene hybrid fiber concrete specimens were prepared and the range of combined fiber content was optimized according to the flow properties to obtain the target hybrid fiber concrete.
2. A hybrid fiber concrete mix design method according to claim 1, characterized in that: After obtaining the target hybrid fiber concrete, the following steps are also included: based on the physical properties and interface geometric characteristics of the steel-polypropylene hybrid fiber concrete, combined with the actual pumping length and pumping height of the engineering site, the combined fiber content and concrete mix ratio of the target hybrid fiber concrete are directionally adjusted according to the fluidity test.
3. A hybrid fiber concrete mix design method according to claim 1, characterized in that: The blending amount of the combined fiber is not less than 0.35%; the mass ratio of the polypropylene fiber to the steel fiber is 1:
10.
4. A hybrid fiber concrete mix design method according to claim 1, characterized in that: In the functional relationship mathematical model, the safety factor σ is calculated based on the target strength f cu,k Get value; When the target intensity f cu,k <C50, the safety factor σ=1.2; the steel fiber influence coefficient α t Take 0.5 to 0.7 according to the fiber shape; When the target intensity f cu,k >C50, the safety factor σ=1.15; the steel fiber influence coefficient α t Take 0.5 to 1.0 according to the fiber shape.
5. A frame structure, characterized in that: It includes a beam, a column, and a beam-column node arranged between the column and the beam; the beam-column node includes steel bars and concrete wrapping the steel bars, and the concrete adopts the target hybrid fiber concrete obtained by the hybrid fiber concrete mix design method as claimed in claim 1.
6. A construction method of a frame structure as claimed in claim 5, characterized in that: The following steps are involved: Determine the beam-column node locations of the frame structure; Calculating the pumping length and the pumping height, and adjusting the combined fiber content and the concrete mix ratio of the target hybrid fiber concrete so that the concrete has fluidity that meets pumping conditions; Installing a casting template for the frame structure, setting a dense mesh inside the template, embedding strain gauges on the steel bars at the beam-column node positions, and recording the deformation state of the steel bars at the beam-column node positions; pouring the target hybrid fiber concrete into the formwork and vibrating and compacting it; After pouring is completed, moisturizing maintenance is carried out.
7. The construction method of the frame structure according to claim 6, characterized in that: After the step of determining the position of the beam-column nodes of the frame structure, the method further includes the step of selecting some beam-column nodes of the frame structure for finite element modeling, and comparing and analyzing the stress conditions of the beam-column nodes before and after using the target hybrid fiber concrete.
8. The construction method of the frame structure according to claim 6, characterized in that: The step of pouring the target hybrid fiber concrete into the formwork comprises: First, the target hybrid fiber concrete is poured into the template at the position corresponding to the column of the frame structure; after the concrete is initially set, the target hybrid fiber concrete is poured into the template at the position corresponding to the beam of the frame structure and the beam-column node position.
Citation Information
Patent Citations
High-performance graphite steel fiber reinforced concrete and its preparation method
CN115140981B
A modified polypropylene fiber reinforced concrete and its preparation method
CN115872681B
